Management of rhinoceros beetle (Oryctes rhinoceros L.) by biological suppression with Oryctes baculovirus in Andhra Pradesh - Rao, N.B.V. Chalapathi; Snehalatharani, A.; Nischala, A.; Ramanandam, G.; Maheswarappa, H.P. (Journal of Plantation Crops, 2018)
The large scale demonstrations on efficacy of Oryctes baculovirus in managing coconut rhinoceros beetle, Oryctes rhinoceros was carried out in 50 acres each at Borivanka, Kuttuma and Bhiripuram, villages in Srikakulam district and Nagullanka and Atreyapuram villages in East Godavari district of coastal Andhra Pradesh. The release of the virus infected beetles was initiated in April 2012 and continued up to June 2013 and the leaf and spindle damage were recorded at three months interval up to twelve months. Before the release of baculovirus infected beetles, per cent of leaf damage due to beetles ranged from 12.5 to 35.5 and spindle damage ranged from 33.3 per cent to 45 per cent. After one year of release of baculovirus infected beetles, leaf damage decreased and ranged from 6.8 to 18.5 per cent and the spindle damage also reduced and ranged from 7.5 to 13 per cent in the mass demonstration villages. In plantations of coconut where application of insecticides is hazardous, biological control with baculovirus infected beetles holds importance.